The relationship between demands for lung cancer screening and the constructs of health belief model: a cross-sectional survey in Hefei, China. Issue 8 (14th September 2018) - Lu, Man-Man; Zhang, Tao; Zhao, Lin-Hai; Chen, Gui-Mei; Wei, Dong-Hua; Zhang, Jun-Qing; Zhang, Xiao-Peng; Shen, Xing-Rong; Chai, Jing; Wang, De-Bin
Abstract: The aim of investigation is to explore the relationship between demands for lung cancer screening (LCS) and the constructs derived from the health belief model (HBM) in Hefei. The study collected data about socio-demographics, health beliefs in and demands for LCS during early June to later July 2015. By constructing a LCS demands HBM constructs, it calculated indices of demands for LCS (DSI) and HBM constructs, which include perceived risk (PR) and seriousness (PS) of the cancers; and perceived effectiveness (PE), benefits (PB) and difficulties (PD) of the screening. It also performed descriptive and multivariate regression analysis of the demands and the HBM constructs. The amount of 823 respondents participated and completed the survey. 6.4% of them had ever undertaken LCS, whereas 60.1% of them expressed willingness to accept the service of LCS if it is free. In multiple regression analysis which used weights in calculating the HBM construct indices, education displayed significant positive associations with DSI ( p = .044), and most of HBM constructs indices (PSI, PRI, PBI, and PDI) were statistically significant with DSI ( p < .05). HBM-based constructs regarding LCS have important effects on demands for the service, and may provide effective paths to cancer screening promotion.